State and Problems of Grey Literature Management In Academic Libraries - Khuntong, Romchat; Manmart, Lampang (Journal of Information and Learning [JIL], 2020)
The purpose of this research was to study the state and the problems of the grey literature management by using qualitative research methods, The data were collected from 11 informants, including librarians and library staff responsible for information management, by means of a semi-structured interview, and they were analyzed qualitatively. The results of this study indicated that 1) the state of grey literature management in academic librarie consisted of general information of key informants, information about libraries and grey literature in libraries, that 2) the management process of grey literature in public university libraries was comprised of compilation, storage and cataloging, accessibility and searching, that 3) problems of grey literature management in public university libraries consisted of management, compilation, storage, cataloging, accessibility, and searching issues, and that 4) grey literature services in public university libraries consisted of borrowing, inter library loan, reserved book, reference and research services, serving various types of information resources in the library, especially grey literature, online public access catalog service, seats for read and study, and photocopying.